IMPLEMENTASI ASAS HUKUM ADMINISTRASI DALAM PENGELOLAAN SUMBER DAYA KESEHATAN DI INDONESIA - Hotmaria Hertawaty Sijabat (CV. Adiba Aisha Amira, 2025)
The implementation of administrative law principles in health resource management in Indonesia is a strategic step to ensure effective, efficient, and equitable health services. The use of administrative law principles, such as accountability, transparency, legal certainty, fairness, efficiency, and effectiveness, plays an important role in realising responsible and community-oriented health governance. Despite various efforts, challenges such as limited resources, infrastructure, and bureaucratic constraints remain obstacles to implementation. In order to create a sustainable health system, continuous monitoring and evaluation in accordance with administrative law principles are necessary to ensure that every policy and implementation provides maximum benefits for all Indonesians.